Hopping backward to move forward: Single-leg backward hopping can better detect decreased quadriceps strength induced by a fatigue protocol compared to forward and vertical hopping - Yu Song; Lauren Salsgiver; Kaden Van Valkenburg; Natalie Christofferson; Yessica Lo; Zhichen Feng; Brenna McGuinness; Boyi Dai (Journal of Sport and Health Science)
Background: Deficits in quadriceps strength of the injured leg have been observed in patients following anterior cruciate ligament (ACL) reconstructions and may contribute to ACL re-injury risk. Single-leg forward hopping is a widely used task for assessing knee function in patients following ACL reconstructions as it has been shown not to be particularly challenging to the knee. This study aimed to quantify the effect of decreased quadriceps strength induced by a fatigue protocol on hopping performance and lower limb mechanics in single-leg forward, vertical, and backward hopping. Methods: Thirty-four injury-free participants performed single-leg forward, vertical, and backward hopping on both legs pre- and post-fatigue, with 1 leg experiencing a fatigue protocol. Peak moments, power, and work of hip, knee, and ankle joints were quantified during the jumping phase. Hopping performance and bilateral asymmetries in performance were assessed. Results: Single-leg backward hopping demonstrated the greatest knee moments, power, and work compared to forward and vertical hopping, regardless of leg and fatigue. Fatigue protocol resulted in significantly less knee moments, power, and work, and decreased performance of the fatigued leg among all tasks. Bilateral symmetries in hopping performance decreased in post-fatigue, with the greatest decrease in backward hopping. Conclusion: The greater sensitivity of the backward hopping to detect quadriceps fatigue suggests it may act as a better or at least an additional metric to evaluate quadriceps strength deficits. The findings may contribute to the development of a clinically applicable and valid strength assessment to monitor the rehabilitation progress in patients following ACL reconstructions.